Historical Study of Girl Child Education in Ghana (1828-2014): A Review of Basel Mission Educational Policy - Asare-Danso, Seth (International Journal of Scientific Research and Management (IJSRM), 2017)
Universal access to quality basic education is a key global developmental issue. However, despite the efforts being made by governments and stakeholders in education to increase girls’ access to basic education, it remains an elusive goal.  This paper focuses on girls’ education in Ghana, which was introduced by the Basel Mission, sustained by colonial and post-colonial governments, but continues to face challenges under the current Ghanaian educational system.  A qualitative research paradigm was adopted for the study, using a historical research design.  Data were collected using observations, interviews and content analysis of educational policy documents.  The research findings revealed that girl-child education was introduced by the Basel Mission based on its theology of marriage and family. This educational legacy was sustained and promoted by colonial and post-colonial governments in Ghana.  However, girl-child education faces many challenges, which have institutional, cultural and social dimensions. The paper recommends that NGO’s, civil society groups, philanthropic organisations and individuals complement government efforts towards the promotion of girl-child education in fulfilment of the Millennium Development Goal 3 which seeks to promote gender equality.